ChemInform Abstract: Iridium(III)‐Catalyzed Direct Arylation of C—H Bonds with Diaryliodonium Salts. Issue 9 (February 2016) - Gao, Pan; Guo, Wei; Xue, Jingjing; Zhao, Yue; Yuan, Yu; Xia, Yuanzhi; Shi, Zhuangzhi
Abstract: A novel method for the direct arylation of sp 2 and sp 3 C—H bonds in ketoximes, nitrogen‐containing heterocycles, a wide range of arenes, and olefins is developed.